Stress Levels and Nutritional Status in Adolescents - M. Haikal Emirza A'la; Zulia Setiyaningrum (ANTHOR: Education and Learning Journal, 2026)
Background: Stress is one of the psychological factors that can influence adolescents’ nutritional status through changes in eating behavior. Adolescents with high stress levels tend to experience changes in appetite, either increased or decreased, which may lead to overnutrition or undernutrition. Adolescence is a critical period marked by physical and emotional changes, making individuals more vulnerable to stress and nutritional problems. Objectives: This study aimed to determine the relationship between stress levels and nutritional status among adolescents at SMA Batik 1 Surakarta. Methods: This study employed a cross-sectional design with an observational analytic approach. A total of 76 respondents were selected using proportionate stratified random sampling. Stress levels were assessed using the Depression Anxiety Stress Scale (DASS-21) questionnaire, while nutritional status was determined using Body Mass Index for age (BMI for age), calculated from weight and height measurements. Data were analyzed using the Spearman Rank test. Results: Most respondents had normal stress levels (59.2%) and normal nutritional status (69.7%). However, 40.8% of respondents experienced stress and 30.3% had nutritional problems. The analysis revealed a significant relationship between stress levels and nutritional status (p=0.014) with a correlation coefficient of r = -0.280, indicating a weak negative correlation. Conclusion: There is a significant relationship between stress levels and nutritional status among adolescents. Adolescents are encouraged to manage stress effectively and maintain a balanced diet to achieve optimal nutritional status.